Managing change in constant evolving sustainable energy market: An exploratory study of motivators, enablers, and barriers - Ali, Husniya M.A.; Ajmal, Mian M.; Gunasekaran, Angappa; Helo, Petri T. (Elsevier, 2019)
Change management (CM) has been a persistent subject among organizations. The basic arguments originate from how and why organizations manage changes. However, CM is paramount for the success and survival of an organization in both highly competitive local and evolving global markets. The general perception of change usefulness or the aims of CM varies among stakeholders, namely employees, top management, as well as customers and governments. Against this backdrop, the current study explores the issue and identifies the motivators, enablers, and barriers of CM in the energy sector by focusing on different stakeholder categories: customers, employees, top management, and government. In addition, CM-related critical facilitating and barricading factors are explored with a structured method from all stakeholders’ perspective. A total of 75 face-to-face interviews were carried out in four different big energy organizations where information was extracted and coded in commonality analysis. The findings concluded that all stakeholders hold a common perception that community welfare/lifestyle, environmental aspects, and country brand/image are the top motives, along with effective/transparent communication, willingness, and flexibility serving as enablers. Additionally, global stability, fear, and change complications are among the main challenges facing CM. With special consideration to each stakeholder, a wide-range commonality analysis demonstrates all stakeholders’ perceptions of what drives, inhibits, and facilitates CM initiatives. It would be more beneficial for energy companies to balance all anticipations of stakeholders to perform successful and sustainable CM. This study is among the first in the region in the energy sector to adopt a broad stakeholder perspective for motivators, enablers, and barriers of CM towards green energy.
Keywords: Change management; Stakeholders; Sustainable energy; Motivators; Enablers; Barriers; UAE; fi=Tuotantotalous|en=Industrial Management|